Identifying Food Intake in Pregnant Women Using the Food Recall Method as an Effort to Prevent Stunting - Uswatun Hasanah; Susanti Susanti; Nur Hayati; Urtiati Urtiati (Jurnal EduHealth, 2026)
Urgency: Pregnant mother is group necessary targets​ get guidance or information in implementation Balanced Nutrition Guidelines: The nutritional status of pregnant women is a focus of attention in community nutrition improvement activities due to its significant impact on the condition of the fetus they are carrying, Objective : to view Intake Overview Food and AKG Macro and micro in mothers pregnant in the region Work Community Health Center Rasana'e Timur City of Bima. Method: study descriptive quantitative, sample of 30 mothers pregnant at the Community Health Center taste east city bima. Ekhnik taking accidental sampling, instrument study food recall sheet and data analysis using analysis table manual nutrition and SPSS, Results: 30 mothers pregnant women aged 20-40 years, age pregnancy part big in the 2nd trimester, Education partly big finish high school level and gravida status ≤ 3 times. Intake energy (calories), substances nutrition macro and some substance gzi micro still <80% of the AKG. Only intake of vitamin B9 and iron iron that is >80% of the RDA. Conclusion: Nutritional status Mother pregnant who becomes respondents everything No at risk of KEK. Average intake energy, substances nutrition macro and micro Still less than <80% of the Recommended Daily Intake (RDA). Intake of Vitamin B9 and other substances iron that is ≥ 80% of the RDA. It is needed activity education For increase knowledge about importance intake substance nutrition that must be consumed by a person Mother pregnant For health mother and child in condition limited,